Interview with Brent Barry of S.C.A.R.A.B. [Architecture fraternity], October 25, 1969 (1969)
[00:00:06] Introduction of Brent Barry, president of SCARAB, honorary architecture service fraternity [00:01:02] Barry tells of numerous architecture community services downtown [00:01:55] Interviewer, McCaleb, asks about a bridge that was designed as a senior project and maintained by architecture students [00:02:38] Barry talks about mission plaza temporary mall project [00:03:30] Barry talks about potential kiosk in front of library and increased communications between architects, engineers, and city planning students [00:04:40] Interviewer asks Barry about the point of view that architects hold about student community service [00:05:18] Interviewer begins to wrap up interview